Radio Observations of Coronal Mass Ejections: Space Weather Aspects - Vourlidas, Angelos; Carley, Eoin P.; Vilmer, Nicole (Frontiers in Astronomy and Space Sciences, 2020)
We review the current state-of-affairs in radio observations of Coronal Mass Ejections (CMEs) from a Space Weather perspective. In particular, we examine the role of radio observations in predicting or presaging an eruption, in capturing the formation stages of the CME, and in following the CME evolution in the corona and heliosphere. We then look to the future and identify capabilities and research areas where radio observations---particularly, spectropolarimetric imaging---offer unique advantages for Space Weather research on CMEs. We close with a discussion of open issues and possible strategies for enhancing the relevance and importance of radio astronomy for Space Weather science.